Bioaccumulation and trophic transfer of Cd in commercially sought brown smoothhound Mustelus henlei in the western coast of Baja California Sur, Mexico. (February 2020) - Pantoja-Echevarría, Laura María; Marmolejo-Rodríguez, Ana Judith; Galván-Magaña, Felipe; Arreola-Mendoza, Laura; Tripp-Valdéz, Arturo; Verplancken, Fernando Elorriaga; Sujitha, S.B.; Jonathan, M.P.
Abstract: A study on cadmium concentration in Mustelus henlei (liver and muscle) was carried out in an area influenced by natural phosphorite deposits and coastal upwelling. Our results indicate that liver (0.96 μg/g) concentrations were higher compared to the muscle (0.040 μg/g) suggesting it is on the safer level for human consumption. The male/female ratio indicates higher values (based on liver & muscle) in males (0.899 μg/g), which contributes to these differences in concentration. Higher values in the liver (0.96 μg/g) is due to the influence of phosphorite deposits in the region as well as the high metabolic activity. The other important factor responsible for these high Cd values are the prey, which also poses high values and is well supported by the biomagnification (1.08 & 4.57) of this element. The study also benefited in evaluating the environmental conditions for this particular species and elemental concentration in relation to human health. Graphical abstract: Unlabelled Image Highlights: Cd concentrations in brown smoothhound shark species and toxicology issues Cadmium levels were below in muscles in the species than the permissible limits of the Mexican government. Biomagnification in preys indicate magnification along food chain.